Uji Efektivitas Beberapa Konsentrasi Larutan Pestisida Nabati Ekstrak Daun Mimba (Azadirachta indica) Dalam Mengendalikan Hama Wereng Batang Coklat (Nilaparvata lugens) Pada Tanaman Padi Varietas Inpari 32 - Furnawanty, Yunita A; Ritawati, Sri; Saylendra, Andree; Rumbiak, Julio E. R (JURNAL BUDIDAYA PERTANIAN, 2025)
Neem (Azadirachta indica) is a type of forest tree where almost all parts of the plant, such as the stem, leaves and seeds, contain bioactive compounds that can be used as botanical pesticides. The aim of this research was to determine the effective concentration of botanical pesticide solution from neem leaf extract against the mortality of brown planthopper (Nilaparvata lugens) on Inpari 32 rice variety. The study was conducted from February to March 2025 in Kampung Kadupinang, Mandalasari Village, Kaduhejo Subdistrict, Pandeglang Regency, and at the LPHP Laboratory Region 2 Pandeglang, Banten Province. The experiment used a Completely Randomized Design (CRD) with four replications and a single factor, which was the concentration of neem leaf extract botanical pesticide at six levels: M0- (control without treatment), M0+ (control with brown planthopper without treatment), 15%, 20%, 25%, and 30%. Observed parameters included brown planthopper mortality (%), lethal time 50% (LT50), lethal concentration 50% (LC50), fresh weight of rice plants, and dry weight of rice plants. The results showed that the 30% concentration had a highly significant effect on brown planthopper mortality. 30% concentration induced the fastest mortality (144 hours), though it failed to achieve 50% mortality. Fresh weight of rice plants was not significantly affected by the neem leaf extract treatment, with the best average value of 3.54 grams. Dry weight of rice plants was significantly influenced by the neem leaf extract treatment, with the highest average value of 1.56 grams. The fastest brown planthopper mortality occurred at the highest concentration.